Application of the Euro Clonality next‐generation sequencing‐based marker screening approach to detect immunoglobulin heavy chain rearrangements in mantle cell lymphoma patients: first data from the Fondazione Italiana Linfomi MCL0208 trial. (18th May 2021) - Genuardi, Elisa; Romano, Greta; Beccuti, Marco; Alessandria, Beatrice; Mannina, Donato; Califano, Catello; Rota Scalabrini, Delia; Cortelazzo, Sergio; Ladetto, Marco; Ferrero, Simone; Calogero, Raffaele A.; Cordero, Francesca
Summary: Minimal residual disease (MRD) determined by classic polymerase chain reaction (PCR) methods is a powerful outcome predictor in mantle cell lymphoma (MCL). Nevertheless, some technical pitfalls can reduce the rate of of molecular markers. Therefore, we applied the EuroClonality‐NGS IGH (next‐generation sequencing immunoglobulin heavy chain) method (previously published in acute lymphoblastic leukaemia) to 20 MCL patients enrolled in an Italian phase III trial sponsored by Fondazione Italiana Linfomi. Results from this preliminary investigation show that EuroClonality‐NGS IGH method is feasible in the MCL context, detecting a molecular IGH target in 19/20 investigated cases, allowing MRD monitoring also in those patients lacking a molecular marker for classical screening approaches.